Desenvolvimento inicial e tolerância de Senna multijuga e Erythrina crista-galli associada à utilização de turfa em solo contaminado com cobre - Marco, Rudinei de (2015)
Constantly it s identified new areas contaminated by heavy metals. Among these metals, the copper, when it s in high concentrations in the soil can cause toxicity to the environment, being necessary the study of alternatives for the decontamination of contaminated areas. Thus, the aim of this study was to evaluate the initial development and tolerance of Senna multijuga and Erythrina crista-galli associated with the use of peat in soil contaminated with copper. To attend the objectives were conducted three experiments. The first involved the evaluation of growth, tolerance and accumulation of copper in plants of Senna multijuga and Erythrina crista-galli. In the second study evaluated the use of peat (200 mL of peat L-1 of soil) and Erythrina crista-galli in phytoremediation of soil contaminated with copper and the third evaluated the peat (200 mL of peat L-1 of soil) as ameliorating of copper in the soil and the potential of Senna multijuga as phytoremediation species. The results indicate that the copper doses reduced the morphological parameters of the plants of the species studied. The copper absorbed by plants was predominantly accumulated in the root system, being small its translocation to the shoot. Erythrina crista-galli and Senna multijuga don t presented as tolerant species to copper and had low potential metal fitoextrator the soil. The use of 200 ml of peat L-1 of soil is not as efficient as ameliorating of contamination with copper, but enabled increase in morphological parameters.